Studies on the Genetic Origin of Mammalian Mitochondrial RNAs - Aujame, Luke (My University, 1978)
The nature and genetic origin of mammalian mitochondrial poly(A)-containing RNA and tRNAs was examined using isolated mitochondria to label these molecules.
The synthesis of poly(A)-containing RNA by isolated mitochondria from Ehrlich ascites cells and rat liver was studied. Isolated mitochondria incorporate [³H]AMP or [³H]UTP into an RNA species that adsorbed on oligo(dT)-cellulose columns or Millipore filters. Hydrolysis of the poly(A)-containing RNA with pancreatic and T₁ ribonucleases released a poly(A) sequence that had an electrophoretic mobility slightly faster than 4Sℯ. In comparison, ascites-cell cytosolic poly(A)-containing RNA had a poly(A) tail that had an electrophoretic mobility of about 7Sℯ . Sensitivity of the incorporation of [³H]AMP into poly(A)-containing RNA to ethidium bromide and to atractyloside and lack of sensitivity to immobilized ribonuclease added to the mitochongria after incubation indicated that the site of incorporation was mitochondrial. The poly(A)-containing RNA from ascites cell mitochondria sedimented with a peak of about 18S, with much material of higher S value. After denaturation at 70°C for 5 min the poly(A)-containing RNA from both ascites cell and rat liver mitochondria separated into two components of 12S and 16S on a 5-20%. (w/v) sucrose density gradient at 4°C, or at 4° and 25°C in the presence of formaldehyde. Poly(A)-containing RNA from ascites cell mitochondria synthesized in the presence of ethidium bromide sedimented at 5-10S in a 15-33% (w/v) sucrose density gradient at 24°C. The poly(A) tail of this RNA was smaller than that synthesized in the absence of ethidium bromide. The size of the poly(A)-containing RNA (approx. 1300 nucleotides) is about the length necessary for that of mRNA species for the products of mitochondrial protein synthesis.
The sedimentation and electrophoretic properties of Syrian hamster cytosolic and mitochondrial methionyl- and leucyl-tRNAs were compared under denaturing conditions. Mitochondrial leucyl-tRNA could be separated into three species by chromatography on RPC-5. Their apparent molecule weights as determined by polyacrylamide slab gel electrophoresis were 23 000 for one species and 24 000 for the other two compared to the five cytosolic leucyl-tRNA species whose apparent molecular weights ranged from 26 000 to 28 000. Mitochondrial leucyl-tRNAs sedimented more slowly than their cytosolic counterparts, again indicating a lower molecular weight. The apparent molecular weights of the mitochondrial methionyl-tRNA were identical or only slightly lower than their cytosolic counterparts as determined by polyacrylamide slab gel electrophoresis.
Individual tRNAs for arginine, asparagine, leucine, lysine, methionine, proline and valine were charged in isolated rat liver mitochondria and shown to be distinct for their cytosolic counterparts by chromatography on RPC-5. By electrophoresis on urea polyacrylamide slab gels it was found that all these mitochondrial aminoacyl-tRNAs were about 70-76 nucleotides long. The unique mitochondrial asparaginyl- and prolyl-tRNAs, not previously identified in mammalian cells, were shown to hybridize to mtDNA. Mitochondrial leucyl-tRNA was separated into 3 peaks on RPC-5 and the first species was shown to be different than a combination of the other two by molecular size and partial RNase T₁ digestion patterns. Each was coded by a separate gene on mtDNA as shown by partial additivity of hybridization. Separate genes for mitochondrial tRNAmᴹᵉᵗ and tRNAfᴹᵉᵗ, separated by RPC-5 chromatography, were also demonstrated. These results bring to 21 the number of individual tRNAs coded by mammalian mtDNA.
Keywords: Biochemistry; Biochemistry